IMPLEMENTASI PERMENDAGRI NO.2 TAHUN 2016 TENTANG KIA (KARTU IDENTITAS ANAK) DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN MOJOKERTO - Wijaya, Dian; Soniatin; Santosa (Government Studies Departement of Universitas Islam Majapahit, Indonesia, 2021)
So far, proof of a child's identity is only limited to a birth certificate, then through the Minister of Home Affairs Regulation No. 2 of 2016the government issued a policy on KIA (Child Identity Card). Where through the KIA (Child Identity Card) the government hopes that there will beincreasing data collection, protection and public services to realize the best rights for children. Not only for data collection purposes, KIA (CardChild Identity) together with the birth certificate are expected to provide legal certainty and guarantee for the recognition of rights along with:his protection. With the formulation of the problem how to implement Permendagri No. 2 of 2016 concerning KIA (Child Identity Card) in the ServicePopulation and Civil Registration of Mojokerto Regency. This study aims to determine the implementation of Permendagri No. 2 of 2016About KIA (Child Identity Card) at the Population and Civil Registration Office of Mojokerto Regency.The theory used is the theory of Policy Implementation from Edward III which consists of 4 indicators, namely: Bureaucratic Structure, Resources,Disposition and Communication. The research method used in this study is a qualitative descriptive method that describes the phenomenonactually from events in the field. Data collection techniques using interviews, observations and documents related to research.The results of the study indicate that the community is the object of implementing the policies contained in the Regulation of the Minister of Home Affairs Number 2The year 2016 regarding Identity Cards is of course urged to realize that current population administration documents are very important andsupport its implementation. of this policy. The government – ??in this case the Department of Population and Civil Registry – has not made enough effortsto raise public awareness effectively.